STUDY ON THE MECHANICAL PERFORMANCE AND FAILURE MODE OF CLINCHING JOINT - ZHOU LuYao; LV Jie; LU ShanBin (Jixie qiangdu)
The mechanics behavior and failure characteristics of clinching joint specimens were investigated through the quasi-static tests and dynamic tests of single clinching joints under cross tension,lap shear and couch peel conditions,and also through the quasi-static tests with different loading angles（ 0 °,30 °,45 °,60 ° and 90 °）. The test results show that,the joint strength becomes greater while shear / tensile ratio increases,but the extensibility of clinching joints exhibits no obvious rule.Button separation happened in cross-tension tests; neck fracture in lap-shear tests; both two failure modes happened in couchpeel tests either separately or simultaneously. All clinching joints have strain rate effect under three typical conditions,i. e. the peak forces of all dynamic tests were higher than the corresponding ones of quasi-static tests.